Lost in translation? Comparative education research and the production of academic knowledge. Issue 2 (4th March 2018) - Mazenod, Anna
Abstract: The worth of academic knowledge tends to be tested against global metrics of citations and articles published in high-ranking English language academic journals. This paper examines academic knowledge production in three local fields of research with different national languages (English, Finnish and French). It focuses on knowledge production on the topic of apprenticeship where there are distinctive differences in the three local research fields and the associated patterns of academic publication over a 15-year period. The findings suggest that publication patterns are still largely tied to the respective national languages. Concerns are raised about the limited visibility of non-Anglophone local contexts and conceptual frameworks as filtered through global academic knowledge production processes. The language practices in the production of academic knowledge need to be challenged to ensure that knowledge from these sources is not lost in translation or in the re-contextualisation for global audiences.